Differential Index-Hospitalization Cost Center Impact of Enhanced Recovery After Surgery Program Implementation. Issue 6 (June 2020) - Najjar, Peter A.; Fields, Adam C.; Maldonado, Luisa J.; Ward, Andrew; Bleday, Ronald
Abstract : BACKGROUND: Most hospitals in the United States are reimbursed for colectomy via a bundled payment based on the diagnosis-related group assigned. Enhanced recovery after surgery programs have been shown to improve the value of colorectal surgery, but little is known about the granular financial tradeoffs required at individual hospitals. OBJECTIVE: The purpose of this study is to analyze the index-hospitalization impact on specific cost centers associated with enhanced recovery after surgery implementation for diagnosis-related groups commonly assigned to patients undergoing colon resections. DESIGN: We performed a single-institution retrospective, nonrandomized, preintervention (2013–2014) and postintervention (2015–2017) analysis of hospital costs. SETTING: This study was conducted at an academic medical center. PATIENTS: A total of 1297 patients with diagnosis-related group 330 (colectomy with complications/comorbidities) and 331 (colectomy without complications/comorbidities) were selected. MAIN OUTCOME MEASURES: The primary outcome was total index-hospitalization cost. Secondary outcomes included specific cost center expenses. RESULTS: Total median cost for diagnosis-related group 330 in the pre-enhanced recovery after surgery group was $24, 111 ($19, 285–$28, 658) compared to $21, 896 ($17, 477–$29, 179) in the enhanced recovery after surgery group, p = 0.01. Total median cost for diagnosis-related group 331 in the pre-enhanced recovery after surgery group was $19, 268 ($17, 286–$21, 858) compared to $18, 444 ($15, 506–$22, 847) in the enhanced recovery after surgery group, p = 0.22. When assessing cost changes after enhanced recovery after surgery implementation for diagnosis-related group 330, operating room costs increased ( p = 0.90), nursing costs decreased ( p = 0.02), anesthesia costs increased ( p = 0.20), and pharmacy costs increased ( p = 0.08). For diagnosis-related group 331, operating room costs increased ( p = 0.001), nursing costs decreased ( p < 0.001), anesthesia costs increased ( p = 0.03), and pharmacy costs increased ( p = 0.001). LIMITATIONS: This is a single-center study with a pre- and postintervention design. CONCLUSIONS: The returns on investment at the hospital level for enhanced recovery after surgery implementations in colorectal surgery result largely from cost savings associated with decreased nursing expenses. These savings likely offset increased spending on operating room supplies, anesthesia, and medications. See Video Abstract at http://links.lww.com/DCR/B204 . IMPACTO DE LA IMPLEMENTACIÓN DEL PROTOCOLO DE RECUPERACIÓN MEJORADA DESPUÉS DE CIRUGÍA EN EL COSTO DE LA HOSPITALIZACIÓN ÍNDICE EN CENTROS ESPECÍFICOS: ANTECEDENTES: La mayoría de los hospitales en los Estados Unidos son reembolsados por la colectomía a través de un paquete de pago basado en el grupo de diagnóstico asignado. Se ha demostrado que los programas de recuperación después de la cirugía mejoran el valor de la cirugía colorrectal, pero se sabe poco sobre las compensaciones financieras granulares que se requieren en los hospitales individuales. OBJETIVO: El objetivo de este estudio es analizar el impacto del índice de hospitalización en centros de costos específicos asociados con la implementación de RMDC para grupos relacionados con el diagnóstico comúnmente asignados a pacientes que se someten a resecciones de colon. DISEÑO: Realizamos un análisis retrospectivo, no aleatorio, previo (2013–2014) y posterior a la intervención (2015–2017) de los costos hospitalarios de una sola institución. AJUSTES: Centro médico académico. PACIENTES: Un total de 1. 297 pacientes con diagnóstico relacionado con el grupo 330 (colectomía con complicaciones/comorbilidades) y 331 (colectomía sin complicaciones/comorbilidades). PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue el índice total de costos de hospitalización. Los resultados secundarios incluyeron gastos específicos del centro de costos. RESULTADOS: El costo medio total para el grupo relacionado con el diagnóstico de 330 en el grupo de recuperación pre-mejorada después de la cirugía fue de $24, 111 ($19, 285– $28, 658) en comparación con $21, 896 ($17, 477– $29, 179) en el grupo de recuperación mejorada después de la cirugía, p = 0.01. El costo medio total para DRG 331 en el grupo de recuperación pre-mejorada después de la cirugía fue de $19, 268 ($17, 286– $21, 858) en comparación con $18, 444 ($15, 506–$22, 847) en el grupo de recuperación mejorada después de la cirugía, p = 0.22. Al evaluar los cambios en los costos después de una recuperación mejorada después de la implementación de la cirugía para el grupo 330 relacionado con el diagnóstico, los costos de la sala de operaciones aumentaron ( p = 0.90), los costos de enfermería disminuyeron ( p = 0.02) los costos de anestesia aumentaron ( p = 0.20) y los costos de farmacia aumentaron ( p = 0.08). Para el grupo 331 relacionado con el diagnóstico, los costos de la sala de operaciones aumentaron ( p = 0.001), los costos de enfermería disminuyeron ( p < 0.001) los costos de anestesia aumentaron ( p = 0.03) y los costos de farmacia aumentaron ( p = 0.001). LIMITACIONES: Este es un estudio de un solo centro con un diseño previo y posterior a la intervención. CONCLUSIONES: El retorno de la inversión a nivel hospitalario para una recuperación mejorada después de la implementación de la cirugía en la cirugía colorrectal se debe en gran parte al ahorro de costos asociado con la disminución de los gastos de enfermería. Es probable que estos ahorros compensen el aumento de los gastos en suministros de quirófano, anestesia y medicamentos. Consulte Video Resumen en http://links.lww.com/DCR/B204 . (Traducción—Dr. Gonzalo Hagerman)